Efektivitas Kebijakan Insentif Pajak Hijau Dalam Mendorong Investasi Swasta - Fazas Hikmah Kasih Telaumbanua (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
Global warming demands a rapid transition to a low-carbon economy. Governments in various countries have implemented green tax incentives (GTIs) as a fiscal instrument to attract private investment to the renewable energy and environmentally friendly technology sectors. This paper aims to analyze the effectiveness of these policies in influencing corporate investment decisions. Through a qualitative approach and literature review, it is found that although tax incentives are able to reduce initial cost barriers, their effectiveness is highly dependent on legal certainty, political stability, and integration with other non-fiscal policies.